Feet representation in modern and contemporary art: their iconographic, symbolic and compositive value - Villaverde Solar, Mª Dolores (Revista Internacional de Ciencias Podológicas, 2008)
Our feet are one of the most important parts of our body. However, they tend to be forgotten by artist and researchers, since other body aspects such as hands, eyes or a smile seem to be more attractive. The goal of this paper is to explain the meaning of feet in arts focused on the symbolic worth of pictures and sculptures from Renaissance to the 20 th Century, and leaving anatomy aside.
Keywords: Foot; Symbolysm; Art